TECHNOLOGICAL PEDAGOGICAL KNOWLEDGE (TPK) OF HISTORY TEACHERS IN JEMBER REGENCY - riski wahyu tantiyo; nurul umamah; mohamad na'im (JURNAL HISTORICA, 2019)
This research aimed at analyzed the technological pedagogical knowledge of the history teachers in Jember Regency. Theory of technological pedagogical knowledge used was the theory by Koehler and Mishra (2006). The components of technological pedagogical knowledge were the knowledge of ICT tools, learning strategies supported by ICT, the use of ICT in scientific research, information skills, facilitators of students, and technical difficulties of students. This research was a descriptive research. The samples used involve 31 history teachers. The data analysis used was descriptive statistical data analysis by using SPSS 21 program for Windows. The results of the descriptive statistical data revealed that the pedagogical content knowledge of the history teachers of Jember Regency as much as 83,9% were at good level. Furthermore, as much as 16.1% were at fair level. Whereas, 0% was at not good, less good levels and very good level. Overall, from the results of descriptive statistical analysis, it obtained the mean value of 3,4686. Based on the results of the research, the technological pedagogical knowledge of the history teachers of Jember Regency were at good level. Teachers are expected to master all four basic competencies of the professional teacher, especially on the competencies of pedagogical and professional. Teachers are also required to be able to integrate pedagogical skills with mastery of information and communication technology, so that learning to students becomes more effective.